90=(4x+12)+(6x+8)

Simple and best practice solution for 90=(4x+12)+(6x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=(4x+12)+(6x+8) equation:


Simplifying
90 = (4x + 12) + (6x + 8)

Reorder the terms:
90 = (12 + 4x) + (6x + 8)

Remove parenthesis around (12 + 4x)
90 = 12 + 4x + (6x + 8)

Reorder the terms:
90 = 12 + 4x + (8 + 6x)

Remove parenthesis around (8 + 6x)
90 = 12 + 4x + 8 + 6x

Reorder the terms:
90 = 12 + 8 + 4x + 6x

Combine like terms: 12 + 8 = 20
90 = 20 + 4x + 6x

Combine like terms: 4x + 6x = 10x
90 = 20 + 10x

Solving
90 = 20 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
90 + -10x = 20 + 10x + -10x

Combine like terms: 10x + -10x = 0
90 + -10x = 20 + 0
90 + -10x = 20

Add '-90' to each side of the equation.
90 + -90 + -10x = 20 + -90

Combine like terms: 90 + -90 = 0
0 + -10x = 20 + -90
-10x = 20 + -90

Combine like terms: 20 + -90 = -70
-10x = -70

Divide each side by '-10'.
x = 7

Simplifying
x = 7

See similar equations:

| 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 | | 11=3u+13 | | (x-67)=x*1.47 | | 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 | | 288/6 | | (3/4)-(9/12) | | 68(x-3)=-2x+35.6 | | 10x+5y+15z= |

Equations solver categories